1999
DOI: 10.1046/j.1365-2613.1999.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of palm vitamin E and ranitidine on the healing of ethanol-induced gastric lesions in rats

Abstract: The effect of palm vitamin E on the healing of ethanol-induced gastric lesion was compared with ranitidine. Fifty-six male rats of Sprague-Dawley species (200-250 g of weight) were randomly divided into three groups (N = 14). Gastric mucosal injury was induced by orogastric tube administration of 0.5 ml 100% ethanol. Immediately after induction, Group I (k) rats was fed with a normal diet (control), group II (p) was fed palm vitamin E enriched diet (150 mg/kg food), Group III(r) was treated with ranitidine 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…It has been reported that treatment with melatonin prevents gastric ulcerogenesis and decreases ulcer index (Bandyopadhyan et al, 2001;Bubenik, 2002). Vitamin E in palm oil has also been shown to reduce ethanol-induced gastric ulcer (Jarrin et al, 1999). Taken together, these results corroborate our present finding of an ameliorative action of dates on ethanol-induced gastric ulceration, possibly due to its relatively high content of antioxidant substances.…”
Section: Number Of Ulcers/stomach (A) Severity Per Stomach (B) Lesionsupporting
confidence: 91%
“…It has been reported that treatment with melatonin prevents gastric ulcerogenesis and decreases ulcer index (Bandyopadhyan et al, 2001;Bubenik, 2002). Vitamin E in palm oil has also been shown to reduce ethanol-induced gastric ulcer (Jarrin et al, 1999). Taken together, these results corroborate our present finding of an ameliorative action of dates on ethanol-induced gastric ulceration, possibly due to its relatively high content of antioxidant substances.…”
Section: Number Of Ulcers/stomach (A) Severity Per Stomach (B) Lesionsupporting
confidence: 91%
“…Gastric ulcers induced by ethanol exposure in rats were significantly reduced with the supplementation of PVE at 150 mg/kg in food for 3 weeks [249,250]. The ulcers healing was also accelerated when PVE (150 mg/kg food) was given post-ulcer induction with ethanol [249]. These effects were achieved by retarding the lipid peroxidation induced by ethanol.…”
Section: Effects Of Tocotrienol On Peptic Ulcersmentioning
confidence: 99%
“…Another important protective factor in the gastric mucosa is the mucus covering it [251]. However, the gastric adherent mucus content was unaltered in rats fed with a diet containing various doses of TRF (60, 100, 150, and 300 mg/kg) for 4-8 weeks and administered absolute ethanol even though there was a reduction in gastric lesion index compared to the untreated control [240,242,244,246,249]. A similar finding was also observed in rats given a diet containing αTF (20, 30, 50, and 300 mg/kg) for 4-8 weeks and challenged with aspirin [240,242], which confirms that neither T3 or TF exerts any significant effect on gastric mucus production.…”
Section: Effects Of Tocotrienol On Peptic Ulcersmentioning
confidence: 99%
“…The mucus covers the mucosa of the gastrointestinal tract (Repetto & Llesuy, 2002). The gastric adherent mucus content was unaltered in rats that were fed a diet containing various doses of tocotrienol-rich fraction (60, 100, 150, and 300 mg/kg) for 4-8 weeks and administered absolute ethanol, indomethacin, or aspirin even though there was a reduction in gastric lesion index compared with the untreated control (Jaarin et al, 1999(Jaarin et al, , 2000(Jaarin et al, , 2002Nafeeza et al, 2002;Qodriyah et al, 2002). A similar finding was also observed in rats given a diet containing a-tocopherol (20, 30, 50, and 300 mg/kg) for 4-8 weeks and challenged with aspirin (Jaarin et al, 2002;Nafeeza et al, 2002).…”
Section: Diminished Endogenous Gastroprotective Factorsmentioning
confidence: 99%